Maintenance management of public building: Royal Custom Malaysia / Norfazleen Fakri - Fakri, Norfazleen (Faculty of Architecture, Planning and Surveying, 2008)
Maintenance Management is a combination of several actions in which to retain or restore an item to perform its required action. Royal Custom Malaysia as one of the government sector in Malaysia that has many assets, needs maintenance to prevent the assets from deterioration. Maintenance in Custom building has a different ways of monitor and control which is according to Custom branch. There are two maintenance system presently implemented at Custom: Preventive maintenance and Corrective Maintenance. Aim of this study to propose maintenance management system. To achieve the aim of this study, four objectives have been set, to study the maintenance management system presently implemented. To identify the common problem in maintenance management. To find out the satisfaction level of Custom’s staff which occurring at the Custom building. To improve the maintenance management system for buildings at Custom building. All data analysis had been compile in case of maintenance management system that Custom had been used. To obtain the data the following knowledge acquisition methods were used by interview, questionnaire and observation. Result of the study showed the responds of the Custom staff for the overall building conditions are based on the building which is located at Kelana Jaya, Putrajaya, Kota Bharu and Rantau Panjang. Hence, to improve the current maintenance management system for Custom building, strategic planning has been suggested in order to increase performance, to provide an effective maintenance management, provide control for maintenance activities, improve quality, cost effective satisfaction, and to optimize the maintenance processes for Custom building.